Step-by-step explanation:
Let P be the interior of triangle ABC
Area of ΔABC = Area of Δ APB + Area of ΔBPC + Area of ΔAPC
1/2 x base x height = ( 1/2 x AB x CP )+( 1/2 x BC x EP )+( 1/2 x AC x PD )
1/2 x base x height = ( 1/2 x AB x CP )+( 1/2 x AB x EP )+( 1/2 x AB x PD )
( since AB =BC =CA in an equilateral triangle)
1/2 x AB x height = 1/2 x AB x ( CP+EP+PD)
1/2 x AB x height = 1/2 x AB x ( sum of perpendicular distances from P to each side of a triangle ).
Thus, the height of an equilateral triangle is equal to the sum of the perpendicular distance from point P to each side of the triangle.
Hence proved.